2019
DOI: 10.5114/pm.2019.90804
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ESR1 and ESR2 oestrogen receptor encoding gene and personality traits – preliminary study

Abstract: Introduction: The main objective of the study is to examine the hypothesis claiming a correlation between personality traits measured with the use of the Minnesota Multiphasic Personality Inventory (MMPI-2) personality questionnaire and the expression of the ERα (ESR1) and ERβ (ESR2) encoding gene in patients suffering from depression. Material and methods: The experiment was carried out on a group of 44 individuals with depression. The Polish variant of the MMPI-2 was applied with the aim of assessing persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…They also play a role in non-genomic cell signaling (the so-called rapidness of action) (Vargas et al, 2016 ; Dovey and Vasudevan, 2020 ). Therefore, ERs are essential for CNS development by regulating neuronal and glial proliferation, migration, differentiation, activation, and apoptosis of neurons (Talarowska et al, 2019 ). By the use of techniques, such as RT-PCR and Northern and Western blot analyses, it was found that many genes are estrogen regulated.…”
Section: Estrogen and Progesterone Receptors In The Regulation Of Soc...mentioning
confidence: 99%
“…They also play a role in non-genomic cell signaling (the so-called rapidness of action) (Vargas et al, 2016 ; Dovey and Vasudevan, 2020 ). Therefore, ERs are essential for CNS development by regulating neuronal and glial proliferation, migration, differentiation, activation, and apoptosis of neurons (Talarowska et al, 2019 ). By the use of techniques, such as RT-PCR and Northern and Western blot analyses, it was found that many genes are estrogen regulated.…”
Section: Estrogen and Progesterone Receptors In The Regulation Of Soc...mentioning
confidence: 99%